Long‐term peripheral immune cell profiling reveals further targets of oral cladribine in MS. Issue 11 (1st October 2020) - Moser, Tobias; Schwenker, Kerstin; Seiberl, Michael; Feige, Julia; Akgün, Katja; Haschke‐Becher, Elisabeth; Ziemssen, Tjalf; Sellner, Johann
Abstract: Objectives: To expand the knowledge about the immunological consequences of cladribine (CLAD), a pulsed immune reconstitution therapy approved for active multiple sclerosis (MS), beyond the known short‐term effects on peripheral immune cell subsets. Methods: In this study, we characterized depletion and restitution kinetics as well as cytokine profiles of peripheral immune cell subsets in 18 patients with MS following treatment with oral CLAD. The methods involved blood collection prior to CLAD and every three months over a period of 24 months, and extensive characterization of various immune cells subsets by multiparametric flow cytometry. Results: We found a selectivity of CLAD towards central memory T cells and memory B cells and detected a hyper‐repopulation of maturing B cells. Counts of classical (−65%) and various nonclassical TH17 cells (−84% to −87%) were markedly reduced 24 months after treatment start, and were comparable with depletion rates of class‐switched memory B‐cell phenotypes (−87% to −95%). The nadir of TH cells was more pronounced in the second treatment year. We observed a proportional surge of CD20 T‐cell subsets and an expansion of regulatory T, B and NK cells. Natural killer T cells (NKT) were only depleted in year two and did not recover. Interpretation: Peripheral immune cell profiling revealed more differentiated insights into the immunological effects of CLAD. While some immune cell subsets expanded, we also observed additive depleting effects after the second treatment course. Further studies are required to elucidate whether these changes are paramount for the consistent and prolonged disease‐modifying effect of CLAD.